1994
DOI: 10.1055/s-2007-1021106
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of Isokinetic Peak Torque and Angle at Peak Torque in the Shoulder Joint

Abstract: Adequate reliability studies of knee flexion and extension are currently available for isokinetic measurements, but not for the shoulder joint. For this reason, this study examines the variability (%) in the determination of peak torque (PT) and the angle at peak torque (AP) in the test-retest procedure. Differentiation is made between the various types of work (concentric, isometric, eccentric) and the degrees of freedom in the shoulder joint (flexion/extension, abduction/adduction, external rotation/internal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
35
1
5

Year Published

1996
1996
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 22 publications
1
35
1
5
Order By: Relevance
“…Three studies 20,21,27 did not report the plane of the shoulder position. Seven studies 2,15,21,27,32,35,38 reported both relative and absolute indices of reliability, but 7 studies 11,25,33,34,[39][40][41] reported only relative indices.…”
Section: Methodological Quality Of the Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Three studies 20,21,27 did not report the plane of the shoulder position. Seven studies 2,15,21,27,32,35,38 reported both relative and absolute indices of reliability, but 7 studies 11,25,33,34,[39][40][41] reported only relative indices.…”
Section: Methodological Quality Of the Studiesmentioning
confidence: 99%
“…The highest QAREL rating was 6/11, with an average of 4.2 ± 1 (range 2-6). Numbers and methodological quality of studies dealing with supine and standing positions were poor: 6 studies 11,20,26,33,34,40 for 3 positions, with QAREL scores from 2 to 4. Individual QAREL scores for each included study are reported in Table 2.…”
Section: Methodological Quality Of the Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The subject's thigh and pelvis were stabilized with dynamometer straps to eliminate any facilitating movements. Before the test each subject flexed the knee to the maximum and performed three submaximal flexion and extension movements at the knee joint to get acquainted with a given load [10].…”
Section: Methodsmentioning
confidence: 99%